Structure of epitaxial CoSi2 films on Si(111) studied with low-energy electron diffraction (LEED) - Starke, Ulrich; Schardt, Judith; Weiss, Wolfgang; Rangelov, Georgi; Fauster, Thomas; Heinz, Klaus (Surface Review and Letters, 1998)
Expitaxial films of CoSi2 on Si(111) were investigated by low-energy electron diffraction. Films of approximately 12 Angstrom thickness were prepared by simultaneous deposition of Co and Si and subsequent annealing. The films were found to crystallize in CaF2 structure in (111) orientation. Two (1 x 1) phases of different stoichiometry exist. The surface phase that contains more Co is found to be a CoSi2(111) bulklike structure terminated by a Si-Co-Si trilayer. The Si-rich phase is terminated by an additional nonrotated silicon bilayer with the lower silicon atoms bound to cobalt in the first CoSi2 layer. Consequently, these cobalt atoms have an eightfold coordination. Due to the lattice mismatch the silicide films are expanded by 0.5% in the lateral direction and contracted by 1.4% in the vertical direction.